Implementasi Projek Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Hartina; Siligar, E.I Pusta (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study has the urgency to examine how the implementation of the Pancasila Student Profile Strengthening Project (P5) at SDN Madugondo serves as a strategic effort to shape students’ character in line with the direction of the Merdeka Curriculum policy. The research employed a descriptive method with a qualitative approach through observation, semi-structured in-depth interviews, and documentation techniques. The researcher acted as the key instrument in observation, while informants were purposively selected, consisting of the Principal, Homeroom Teachers, Project Coordinator Teacher, and four students from grades 1, 3, and 4. Data analysis was conducted using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that during the planning stage, teachers prepared project dimensions and themes relevant to sustainable lifestyles; in the implementation stage, coordination was carried out with the principal and other teachers, dissemination was provided to parents and students, and evaluation instruments were developed; whereas in the evaluation stage, teachers observed the learning process, used assessment rubrics, and evaluated the achievement of the Pancasila Student Profile dimensions. The practical implementation of this study demonstrates that P5 is not merely a formal program, but can also be sustainably integrated into the school culture through collaboration among teachers, parents, and students. Scientifically, the results of this study enrich the discourse on implementation strategies of the Merdeka Curriculum, particularly at the elementary school level. Keywords: Implementation; Pancasila Student Profile Strengthening Project; Elementary School